Proses Fonologis Bahasa Dayak Suhaid: Kajian Teori Optimalitas Dan Generatif Transformasional - Dhion Meitreya Vidhiasi (Saintara: Jurnal Ilmiah Ilmu-Ilmu Maritim, 2020)
Word formation process in one language often produces sound changes (phonological) which caused by the sound of a morpheme adjacent to another sound of another morpheme. This paper aims to discuss the phonological processes in Dayak Suhaid language. The writer uses two approaches in analyzing the process, those are Optimality Theory and Generative Transformational Theory. Optimality theory is used to determine the phonetic form (output) from many candidates and constraints. Generative Transformational theory is used to explain the sound changes processes. The data used in this paper are taken from a Dayak Suhaid native speaker. The result of the analysis shows that Optimality theory and Generative Transformational theory is relevant to explain the phonological process in Dayak Suhaid language such as the deletion of obstruent and insertion of weak vowel [ə].